Plerixafor in Patients with Decreased Mobilizing Ability of Autologous Hematopoietic Stem Cells - MA Kucher; МS Motalkina; ОU Klimova; ЕV Kondakova; ОB Kalashnikova; SМ Alekseev; DV Motorin; DV Babenetskaya; EI Podol’tseva; NB Mikhailova; МА Estrina; ЕV Babenko; et al. (Клиническая онкогематология)
Background & Aims. Autologous hematopoietic stem cell transplantation (autoHSCT) is an effective treatment for patients with malignant lymphoproliferative disorders, multiple myelomas and solid tumors sensitive to chemotherapy. Harvesting of hematopoietic stem cells (HSC) prior autoHSCT may be ineffective in up to 40 % of cases, if aggravating factors are present. One of methods to overcome the reduced mobilization ability is to include a CXCR4-inhibitor (plerixafor) to the mobilization strategies. The aim was to evaluate the efficacy and safety of different autologous HSC mobilization regimens containing plerixafor.